Vilniaus universitetas bibliografiniuose šaltiniuose - Jurčiukonienė, Apolonija; Petrauskienė, Zofija Milda (Knygotyra, 2026)
The 400 year history of the Vilnius university has found reflection in many publications. The first attempts to bibliography the University history were made in the XVII century publications which, besides the material on the University activities, gave the information about the University professors and their scientific works. With the rise of bibliographic activity there appeared some prominent publications, recording the material about Vilnius University. Those were the works by A. Jocher, J. Bielinski, L. Finkel, L. Janowski and some others. The most important Lithuanian works about the old Vilnius university were published by S. Baltramaitis and V. Biržiška. The history of the Vilnius university, reopened in 1919, is shown in the publications of Stephen Bathory university and the bibliographical index compiled by M. Ambros, presenting the material about the University, given in the chronologically-subject order. The Lithuanian University which existed at the same time in Kaunas, published its own bibliographical indices; the University professors' publication index was published by P. Dilys in Chicago. Material about the University activities was also published in the journal „Bibliographical news" („Bibliografijos žinios").The Soviet Lithuanian bibliographers have collected much material about the history of education and science in Lithuania, which is published in independent publications. The most important of this kind are: „The Soviet Lithuanian Higher Schools", „Vilnius University. Bibliography. 1940–1977", which register the material giving the present-day evaluation of the University's 400 year history. Special bibliographies as well as bibliographical data, collected in monographies and articles on the history of science by Lithuanian scientists, can also be regarded as bibliographical sources about the Vilnius University.